Persistent Aura with Small Occipital Cortical Infarction: Implications for Migraine Pathophysiology - Sam Thissen; Peter J. Koehler (Case Reports in Neurology, 2014)
Objective: The pathophysiology of migraine with aura is thought to be related to cortical spreading depression and cortical hypersensitivity, in which inhibitory interneurons may play a role. Persistent migraine aura (PMA) without infarction is defined as auras that last longer than 1 week in the absence of infarction. We describe a case of persistent aura with a small occipital cortical infarction and discuss implications of this case and PMA for pathophysiological concepts of migrainous auras. Methods: We present a case and discuss the implications for pathophysiological concepts. Results: The case presented cannot be diagnosed as PMA as the patient was found to have an occipital cortical infarction with hypoactivity on fluorodeoxyglucose-positron emission tomography. Nevertheless, the patient suffered from persistent aura (with infarction). We argue that the infarction may have been responsible for an increased imbalance in one of the primary visual cortex networks that was already hyperexcitable due to the migraine aura condition. Conclusion: PMA with occipital infarction has not been reported previously. We believe the findings of the present case and PMA cases reported in the past may support the intracortical disinhibition hypothesis in migraine.